Effects of different breeding systems on the slaughter and carcass characteristics and taste criteria of pheasants (Phasianus colchicus) - Aysondu, Mehmet Hanifi; Ozbey, Orhan; Esen, Fikret (My University, 2013)
This study was conducted with the purpose of determining the effects of different breeding systems on the slaughter and carcass characteristics and taste criteria of pheasants bred under intensive conditions. With the comparison of the values concerning slaughter and carcass characteristics determined with the slaughter of 16 weeks old pheasants in terms of breeding systems and gender while significant differences were determined in favor of cage system in terms of carcass weights, weights of wings, breasts and edible internal organs and rates of wings and breasts (p<0.05) in terms of gender significant differences were determined in favor of male pheasants in terms of live weight, carcass weight and head, leg, internal organs, edible internal organs, wings and breast weights (p<0.05). Significant differences were also found in terms of taste and general level of liking between the meats of pheasants bred with free range and cage systems but cooked in the same way (p<0.05). In general, the meats of the pheasants bred with free range system were liked more than those of the pheasants bred with cage system. © Medwell Journals, 2013.
Keywords: Breeding systems; Pheasant; Slaughter and carcass characteristics; Taste criteria; Wings